Are the GCC FDI Location Determinants Favorable? - Mina Wasseem (Kiel Institute for the World Economy (IfW), 2007)
Diversifying income sources is one of the main challenges the GCC countries currently face. FDI can be beneficial in this regard. FDI can help the GCC countries gain access to technology, adopt innovation in the production process, obtain new expertise and managerial know-how, and expand production, marketing, transport, and communication networks. Despite the FDI potential benefits to and the FDI potential of the GCC countries, FDI flows declined in absolute and relative terms. This paper examines the question of whether the location determinants are favorable to FDI in the GCC region. Using panel data for the period 1980-2002, panel data model estimates suggest that market size, as measured by real GDP per capita, and trade openness have positive influence on FDI flows, while institutional quality has a statistically significant positive influence when the period 1980-1982 was dropped from the sample period. Surprisingly human capital deters FDI flows.
Keywords: F53; F21; 330; Foreign direct investment; international capital flows; GCC; location advantage; panel data models